Experimental Analysis Of Tribological Performance Of Palm Oil Blended With Hexagonal Boron Nitride Nanoparticles As An Environment-Friendly Lubricant - Abdollah, Mohd Fadzli bin (Springer Nature, 2020)
Expanded worries about the ecological harm brought about by mineral oil-based lubricants have made a developing worldwide trend of advancing vegetable oil as base oil. Along these lines, this paper presents the tribological performance of palm oil blended with hexagonal boron nitride (hBN) nanoparticles as an environment-friendly lubricant. The hBN nanoparticles were 70 nm and were blended with the palm oil at varying concentrations that ranged between 0 and 0.5 vol.%. The samples were blended by using the sonication technique, with the help of an ultrasonic homogenizer. Thereafter, the tribological test was conducted using a four-ball tribometer as indicated by engineering standard testing method (ASTM D4172-94). The surface morphology and chemical composition of the worn surfaces were observed using the scanning electron microscopy (SEM) installed with energy-dispersive X-beam spectroscopy (EDX). Results showed that when hBN nanoparticles were blended with palm oil, the unsteady-state coefficient of friction (COF) was promptly changed to a steady-state condition during the running-in period. However, the higher concentration of hBN nanoparticles causes higher COF. Furthermore, 0.1 vol.% of the hBN nanoparticles in palm oil exhibited lower COF and wear rate compared with the palm oil alone and commercially available engine oil SAE 15W40.